Peningkatan Kemampuan Menulis Teks Ulasan dengan Metode Peta Pikiran: Pengalaman dari Bengkulu Selatan - Rosmaidah; Dafid Hudan Dardiri (Peradaban Journal of Interdisciplinary Educational Research, 2023)
The research aims to assess the aptitude for composing review texts through the employment of the mind mapping method among students of Class VIII C at SMP Negeri 10 Bengkulu Selatan during the academic year 2022/2023. The study adopts a classroom action research design, conducted over two cycles: Cycle I and Cycle II. Each cycle involves stages encompassing planning, implementation, observation, and reflection. Research data comprises student-written scores obtained throughout the instructional period. The analysis of student compositions reveals that the pedagogical approach of teaching review text composition via the mind mapping method yields an enhancement in the mean learning outcomes. This augmentation is evident in the shift from a mean score of 64.4 in Cycle I to an elevated average of 79.75 in the subsequent instructional phase of Cycle II. In conclusion, the pedagogy of teaching review text composition through the utilization of the mind mapping method substantiates an advancement in students' narrative writing proficiency. It is recommended that educators incorporate this method into their instructional practices to foster students' writing skills, particularly concerning review text composition. Tujuan penelitian ini untuk mengetahui kemampuan menulis teks ulasan dengan metode peta pikiran pada siswa kelas VIII C  SMP Negeri 10 Bengkulu Selatan tahun ajaran 2022/2023. Penelitian ini merupakan penelitian tindakan kelas. Penelitian tindakan kelas ini dilakukan dalam dua tahap, yaitu siklus I dan siklus II. Tiap siklus terdiri atas perencanaan, tindakan, observasi, dan refleksi. Data penelitian ini berupa nilai hasil tulisan siswa selama pembelajaran berlangsung. Dari hasil analisis tulisan siswa diketahui bahwa pembelajaran menulis teks ulasan dengan metode peta pikiran dapat meningkatkan rata-ata hasil belajar siswa. Peningkatan dapat dilihat dari hasil tulisan siswa pada siklus I dengan atau-rata 64,4 dan meningkat pada proses pembelajaran siklus II dengan nilai rata-rata mencapai 79,75. Disimpulkan bahwa pembelajaran Pembelajaran menulis teks ulasan dengan menggunakan metode peta pikiran dapat meningkatkan kemampuan keterampilan menulis pengalaman siswa. Disarankan agar guru dapat menggunakan metode peta pikiran ini untuk meningkatkan kemampuan menulis siswa khususnya menulis teks ulasan.